Catch‐related fish injury and catch efficiency of stow‐net‐based fish recovery installations for fish‐monitoring at hydropower plants. (11th December 2017) - Pander, J.; Mueller, M.; Knott, J.; Geist, J.
Abstract: Hydropower‐related damage to fish remains a great challenge, making objective monitoring of turbine‐related fish injury a necessity. The catch of fish at turbine outlets is currently realised by net fishing, but potential catch‐related injuries are largely unknown. Catch efficiency and fish‐friendliness in relation to fish handling, exposure time, floating debris and fish biomass of four fish recovery installations were assessed using seven species. Highly species‐specific lethal and sublethal effects were observed. Exposure time had the strongest effects on catch‐related damage, being up to 150‐fold increase after 12 hr compared to 1 hr. Up to 84% mortality occurred in the most sensitive species Thymallus thymallus L. Besides exposure time, higher current speed and biomass within the net resulted in greater fish damage. To minimise catch‐related effects, keeping emptying periods <1–2 hr and considering the effects of current speed, fish and debris biomass are crucial to increase data comparability among studies.